Pergeseran Paradigma Hukum Investasi Internasional: Menyeimbangkan Perlindungan Foreign Direct Investment (FDI) dengan Kedaulatan Regulasi Negara dalam Konteks Reformasi Perjanjian Indonesia Pasca-BIT - Apriyanti, Elisya Karina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The international investment law regime has shifted from pro-investor Bilateral Investment Treaties (BITs) towards frameworks balancing Foreign Direct Investment (FDI) protection with state regulatory sovereignty. This research examines Indonesia's 2014 termination of 67 BITs and subsequent policy reforms, analyzing the conflict between Investor-State Dispute Settlement (ISDS) mechanisms and the Right to Regulate. First-generation BITs create regulatory chill through expansive arbitral interpretations that restrict developing states' policy space. The Newmont Mining v. Indonesia case exemplifies how ISDS can undermine legitimate Mining Law implementation. Indonesia responded by adopting new-generation investment agreements integrating the Investment Court System (ICS) in the IEU-CEPA, strengthening regulatory sovereignty clauses, and implementing carve-outs for sensitive policy domains. The research affirms that Indonesia's BIT reform strategy asserts sovereignty while ensuring FDI protection applies only to quality investments contributing to sustainable development.